Wormball as a cause of acute intestinal obstruction: a case report and brief review - Agrawal, Himanshu; Kumar, Vivek; Tanwar, Himanshu; Maurya, Shailender Kumar; Kumar, Shubham (International Journal of Scientific Reports, 2024)
Soil transmitted helminthic (STHs) infection are mainly caused by Ascaris lumbricoides (AL) and commonly affect children worldwide and in India by ingestion of embryonated larva. It can cause various gastrointestinal and hepatobiliary complications. We are presenting a case of 25 years old gentleman who presented to emergency department with feature of intestinal obstruction. Patient was subsequently undergoing emergency exploratory laparotomy and obstructing worms were recovered. Patient did well in postoperative period and discharged after deworming with albendazole. There have been multiple reports of AL causing intestinal obstruction in endemic areas. Acutely sick patient presenting in emergency require resuscitation and may require emergency laparotomy followed by deworming with albendazole. In a patient presented with symptoms and signs suggestive of bowel obstruction, ascariasis should be considered as a differential diagnosis for those from endemic areas.